2016
DOI: 10.9787/pbb.2016.4.3.297
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Selected Rice Varieties Adapted in Africa

Abstract: This is an Open-Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited. ABSTRACT Rice varieties developed through the inter-specific crosses between Asian (Oryza sativa L.) and African cultivated rice (O. glaberrima Steud.) have contributed to yield enhancement of African rice. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Previously, our genetic diversity analysis of rice varieties adapted to the environmental conditions in Africa using indica-japonica SNP set 1 revealed that CG14 (Oryza glaberrima) is genetically closely related to japonica, whereas NERICA (New Rice for Africa) varieties, developed from a cross between O. glaberrima and O. sativa, are closely related to indica (Megersa et al 2016). After the development of indica-japonica SNP set 2, we genotyped 83 diverse germplasms using both SNP sets.…”
Section: Snp Verification and Genetic Diversity Analysismentioning
confidence: 99%
“…Previously, our genetic diversity analysis of rice varieties adapted to the environmental conditions in Africa using indica-japonica SNP set 1 revealed that CG14 (Oryza glaberrima) is genetically closely related to japonica, whereas NERICA (New Rice for Africa) varieties, developed from a cross between O. glaberrima and O. sativa, are closely related to indica (Megersa et al 2016). After the development of indica-japonica SNP set 2, we genotyped 83 diverse germplasms using both SNP sets.…”
Section: Snp Verification and Genetic Diversity Analysismentioning
confidence: 99%
“…The Fluidigm SNP genotyping system has automated polymerase chain reaction (PCR) and integrated fluidic circuit (IFC) technology, which automatically mixes PCR reagents through microfluidic channel networks. The indica-japonica SNP assays, based on the Fluidigm system developed in the previous study [16], have been applied to various genetic analyses and molecular breeding, such as bulked segregant analysis (BSA) [17], genetic diversity analysis [18,19], QTL analysis [20][21][22][23], and background profiling [24][25][26]. This Fluidigm SNP marker set has provided a faster and more cost-effective tool than other high-throughput SNP genotyping systems for primary analysis during molecular breeding using inter-subspecific populations, to date.…”
Section: Introductionmentioning
confidence: 99%